1999
DOI: 10.1039/a905094i
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical promotion of catalytic CO oxidation on Pt/YSZ catalysts under low pressure conditions

Abstract: Catalytic CO oxidation has been investigated under low pressure conditions (p B 10~6 mbar) employing porous Pt Ðlms on a solid state electrolyte (yttrium stabilized as catalyst. The samples were ZrO 2 \ YSZ) characterized by impedance spectroscopy and linear sweep voltammetry before rate measurements were conducted in an UHV chamber with a di †erentially pumped mass spectrometer, a Kelvin probe for integral and a photoelectron emission microscope (PEEM) for spatially resolved measurements of the work function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 23 publications
1
46
0
6
Order By: Relevance
“…In our previous papers 5, 6 we have defined two types of electrochemical promotion, based on the assumption that the catalytic activity was a result of a change in the Fermi level of the catalyst during electrochemical polarization of the catalyst. [12][13][14][15][16][17][18] The Fermi level can be changed simply by charging of the electric double layer at the interface catalyst-support ͑change of the outer, Volta potential͒ without electrochemical reaction. Therefore, this kind of electrochemical promotion was called charge-induced ͑CI͒ EP.…”
mentioning
confidence: 99%
“…In our previous papers 5, 6 we have defined two types of electrochemical promotion, based on the assumption that the catalytic activity was a result of a change in the Fermi level of the catalyst during electrochemical polarization of the catalyst. [12][13][14][15][16][17][18] The Fermi level can be changed simply by charging of the electric double layer at the interface catalyst-support ͑change of the outer, Volta potential͒ without electrochemical reaction. Therefore, this kind of electrochemical promotion was called charge-induced ͑CI͒ EP.…”
mentioning
confidence: 99%
“…The change in the work function was measured using the Kelvin probe technique. However, it has been found later [18][19][20][21][22] that work function changes of catalyst with different morphology, measured using a Kelvin probe, may be only a part of the applied polarization or do not change at all. Summarizing the results of Refs.…”
Section: ϭ ⌬⌽ ͓3͔mentioning
confidence: 99%
“…This phenomenon was named NEMCA effect ͑nonfaradaic electrochemical modification of catalytic activity͒ or electrochemical promotion. 4 The NEMCA effect has been demonstrated for more then 50 heterogeneous 2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and one homogeneous 1 catalytic reactions. According to Vayenas et al, [5][6][7][8][9][10] the NEMCA effect can be described by the following parameters.…”
Section: 3mentioning
confidence: 99%
“…Taking into account the considerations described and the published data on the electrochemical promotion, [2][3][4][5][6][7][8][9][10][11][12][13][14] we can define three types of electrochemical promotion depending on values of the faradaic current ͑I͒ and 1. The electrochemical promotion effect is the charge-induced ͑electrostatic͒ change of the strength of chemisorptive bonds at the catalyst-reactant interface ͑CI-effect͒.…”
Section: ⌬⌽ ϭ ⌬ ϩ ⌬ ͓5͔mentioning
confidence: 99%
“…2 The term ''electrochemical promotion'' was first proposed by Pritchard 3 in his response to Vayenas's paper. 2 The NEMCA effect has been demonstrated for more than 50 heterogeneous [3][4][5][6][7][8][9][10][11][12][13] and one homogeneous 14 catalytic reactions. Thus, for example, it was shown that CH 4 oxidation to CO 2 on the Pt/yttria-stabilized zirconia ͑YSZ͒ catalyst can be electrochemically promoted up to five times.…”
mentioning
confidence: 99%